DIS/COMFORTING SHELFIES: TRAVELLING LITERACIES OTHER-WISE IN DISRUPTED TIMES - Fiona Scott; Amélie Lemieux; Kelly C. Johnston (Digital Culture & Education, 2022)
COVID-19 is reshaping working arrangements in traditionally office-based professions. For scholars, these disruptions emphasise the need to examine how literacies travel other-wise (Lemieux et al., forthcoming) through Zoom meetings, shelfie tweets, and bookshelf photographs. Here, we evoke the altered paths that bodies, objects, and ideas are travelling as workers curate, negotiate, and become implicated in ‘zoomentities’. This posthuman, trioethnographic (Breault et al., 2012) piece attempts to map these altered paths. We began by thinking about emergent literacy practices we observed, particularly the composing of shelfies as highly curated, intentional representations of professional selves. In parallel, we attended to the dis/comfort of the shelfies and ‘zoomentities’ we became implicated in and to what was produced in the assemblaging (Johnston, 2019) as disparate things came into relation in our lives. We mapped our thinking by sharing images on Padlet1 (Image 1). The resulting thematic visual essay (Heng, 2020) is accompanied by first-person accounts, to elucidate the theories underpinning these images and help readers better understand our thinking.